Properties and corrosion behaviors of mild steel in biodiesel-diesel blends - Dharma S.; Silitonga A.S.; Shamsuddin A.H.; Sebayang A.H.; Milano J.; Sebayang R.; Sarjianto; Ibrahim H.; Bahri N.; Ginting B.; Damanik N. (Taylor and Francis Inc., 2023)
Alternative fuels; Biodiesel; Corrosion rate; Corrosive effects; Diesel engines; Diesel fuels; Environmental impact; Fossil fuels; Global warming; Low carbon steel; Residual fuels; Bio-diesel blends; Corrosion attack; Corrosion behavior; Diesel fuel blends; Metal surfaces; Non-edible oil; Steel coupon; Surface observation; Steel corrosion